The Self-determined Motivation of Young who Use Facebook to Build Knowledge - Valdivia Yábar, Silvia Verónica (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This paper studies the self-determined motivation among a group of young from an academic program of the National University of the Altiplano of Peru who use Facebook as a platform for collective construction of knowledge. The objective was to determine the level of self-determined motivation of students in learning activities. A mixed approach, qualitative and quantitative, was adopted. A Likert questionnaire and a semi-structured interview were carried out with 15 student volunteers. The results showed that the mean of intrinsic motivation prevails over that of extrinsic motivation and amotivation. Also, the use of Facebook fostered an increase in self-determination.